2021
DOI: 10.1007/s00405-021-07127-3
|View full text |Cite
|
Sign up to set email alerts
|

Low skeletal muscle mass assessed directly from the 3rd cervical vertebra can predict pharyngocutaneous fistula risk after total laryngectomy in the male population

Abstract: Purpose Skeletal muscle mass (SMM) loss and sarcopenia have been identified as risk factors for postoperative complications. The aim of this study was to investigate the relationship between pharyngocutaneous fistula (PCF) formation after total laryngectomy (TL) and SMM assessed from a computed tomography image of the 3rd cervical vertebra (C3). Methods Retrospective study of 86 male patients who underwent TL between 2013 and 2019 in a single institution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Low skeletal muscle mass, sarcopenia, is relatively common (30–50 per cent) in patients who have undergone or are undergoing laryngectomy. 33 , 34 Sarcopenia results in less muscle strength, affects gait, endurance and mobility, and may lead to inactivity that further impacts muscle mass and strength. 35 Limited muscle strength after laryngectomy could be a problem when using the current cardiopulmonary exercise testing protocols, which also calls for smaller increments.…”
Section: Discussionmentioning
confidence: 99%
“…Low skeletal muscle mass, sarcopenia, is relatively common (30–50 per cent) in patients who have undergone or are undergoing laryngectomy. 33 , 34 Sarcopenia results in less muscle strength, affects gait, endurance and mobility, and may lead to inactivity that further impacts muscle mass and strength. 35 Limited muscle strength after laryngectomy could be a problem when using the current cardiopulmonary exercise testing protocols, which also calls for smaller increments.…”
Section: Discussionmentioning
confidence: 99%
“…Swartz et al found a strong correlation between paravertebral and sternocleidomastoid muscle SMA at the C3 level and SMA at the L3 level [29]. However, C3 to L3 conversion formulas can be complex to use in practice, and several studies have directly evaluated outcomes with measurements at C3 [14,15,30]. Limitations of CT images at C3 include dental artefacts and exclusion of part of the sternocleidomastoid muscles or manual approximation of their segmentation due to tumor invasion [14].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia has been recognized as a poor prognostic factor for postoperative complications, rate of chemoradiation completion, and survival in HNC patients [6][7][8][9][10][11][12]. Specifically after total laryngectomy for advanced laryngeal carcinoma, sarcopenia has been shown to predict postoperative wound complications and pharyngo-cutaneous fistulas (PCF) [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A nationwide Dutch study showed a broad range of PCF incidence between the centers of the Dutch Head and Neck Society (NWHHT), which could not be fully explained by the prediction model developed with known risk factors know at that time. More recently also, a preoperative radiological assessed low skeletal muscle mass (SMM) was found to be an independent risk factor for PCF development [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on body composition and especially on SMM has increased. It appears that a low SMM is associated with acute and late adverse events in patients with head and neck cancer during (chemo)radiotherapy [ 20 23 ], flap-related complications [ 24 , 25 ], decreased survival rates [ 26 – 29 ], and PCF [ 18 , 19 ]. This emphasizes the importance of considering SMM in assessing PCF risk.…”
Section: Introductionmentioning
confidence: 99%